INDUCIBILITY OF THYMIDINE KINASE BY THYMIDINE AS A FUNCTION OF INTERPHASE STAGE - Hotta, Yasuo (The Rockefeller University Press, 1965)
Thymidine may act as an inducer of thymidine kinase activity in cells of higher plants. The general response is demonstrable in a randomly developing cell population such as is found in germinating wheat embryos. If a synchronously developing cell population is studied, however, potentially inducible cells are found to be susceptible to the inductive effect of thymidine only during about 10 per cent of the G1 period, and close to the interval when thymidine kinase activity normally appears.